Financial Development, International Capital Flows, and Aggregate Output - von Hagen, Jürgen (Institutional Knowledge at Singapore Management University, 2013)
We develop a tractable two-country overlapping-generations model and show that cross-country differences in financial development can explain three recent empirical patterns of international capital flows: Financial capital flows from relatively poor to relatively rich countries, while foreign direct investment flows in the opposite direction; net capital flows go from poor to rich countries; despite its negative net international investment positions, the United States receives a positive net investment income. International capital mobility affects output in each country directly through the size of domestic investment and indirectly through the aggregate saving rate. Under certain conditions, the indirect effect may dominate the direct effect so that international capital mobility raises output in the poor country and globally, although net capital flows are in the direction to the rich country. We also explore the welfare and distributional effects of international capital flows and show that the patterns of capital flows may reverse along the convergence process of a developing country. Our model adds to the understanding of the benefits of international capital mobility in the presence of domestic financial frictions.